Effectiveness Of Forest Management As Affected By The Land Use Act In Onigambari Forest Reserve, Oluyole Local Government Area Ibadan, Nigeria. - Yusuff , Z .O.; Alamu, L. O. (Advances in Social Sciences Research Journal, 2019)
The growing demands for forest goods and services are putting serious pressure on the resource base, leading to over-exploitation and subsequent forest degradation. In Nigeria both natural and plantation forests could not meet 100 million m3 of the 180 million m3 wood demand in 2000. At present, one of the most challenging problems facing the country is the production of sufficient food and fiber to meet the needs of the ever-increasing population (Peters, 2005). This study examined the effectiveness of forest management in Onigambari forest reserve, Oluyole Local Government Area Ibadan, Nigeria. The study employed a simple random sampling technique to select 43 forest farmers randomly. Descriptive tools such as frequency distribution, percentage, mean, ranking and Pearson product moment correlation (PPMC) was used as inferential statistical tool to determine the forest management performance in the study area while Student T-test was used to test for the significance difference of the relationship between the forest managers and locals. Result showed that mean age of respondents is 39.65 years. A tittle above Forty Eight percent of the respondents were females while 51.16% of the respondents were males, A tittle above Eighteen percent of the respondents were single while 81.40% of the respondents were married. The result of Student t- test revealed that the mean of age is higher than the mean total effects indicating improved performance of age on the total effects in the study area. The p value (0.0000) is smaller than the chosen alpha value (0.05) which has the t-value of 6.840. The result further revealed that deforestation is now becoming history as a result of land use policy on forest management and it has the highest weighted mean score of 2.86 and ranked as the first, followed by the demand of local industries can partially be met second (WMS= 2.74). The result on Pearson product moment correlation revealed that some of the selected factors such as poor participation of people involved in forestry (r= 1.000**; p <= 0.01), use of inexperience foresters (r= 0.262*; p <0.05) and poor conflicts management between local farmers and foresters (r= 0.387*; p < 0.05) respectively exhibited a significant relationship between forest managers and locals/indigenous people. The study recommended that there should be increase in communication among all stakeholders to ensure the harmonization of all interests towards a better use of forest resources, also effective continuous public enlightenment is essential to secure the interest and participation of farmers with an effective mechanism for good governance, equitable benefit sharing, and lastly, conflict resolution mechanism should be established.